Fundamentals of Physics II : Electromagnetism, Optics, and Quantum Mechanics. - Shankar, Ramamurti (Open Yale courses series., 2020)
A beloved introductory physics textbook, now including exercises and an answer key, accessibly explains electromagnetism, optics, and quantum mechanics R. Shankar is a well known physicist and contagiously enthusiastic educator, whose popular online introductory-physics video lectures have been viewed over a million times. In this second book based on his online courses, Shankar explains electromagnetism, optics, and quantum mechanics, developing the basics and reinforcing the fundamentals. With the help of problem sets and answer keys, students learn about the most interesting findings of today's research while gaining a firm foundation in the principles and methods of physics.